Aircraft Selection Using Analytic Network Process: A Case for Turkish Airlines - Ozdemir, Yavuz; Basligil, Huseyin; Karaca, Merve (INT ASSOC ENGINEERS-IAENG, 2011)
Nowadays airway transportation is the fastest type of transportation. With advancement of the aviation technologies, the plane's increased speed, and a lot of companies that entering to the airway transportation sector, leads to the conclusion that rising competition and decreased prices. Such an important sector, each type of investments have to be feasible and logical, e.g. airport location, aircraft purchase, services, crews and their assignment etc. Because of purchasing, renting or chartering aircrafts, their needs for maintenance and having a fleet are the biggest costs for airline companies. For this reason in this paper we study selecting aircraft to purchase for the biggest Turkish airline company, Turkish Airlines using one of the multi criteria-decision making techniques, Analytic Network Process (ANP).
Keywords: aircraft; Analytic Network Process (ANP); decision making; Multi-Criteria Decision Making (MCDM); FUZZY ANP; Computer Science; Engineering